L’administration du désordreGouverner l’hôpital psychiatrique depuis les années 1980 - Tonya Tartour (Revue de la Régulation)
The dissertation examines the recent transformations in the modes of governing the activities of psychiatric hospitals. More specifically, it explores the role of two influential reform processes in France: the introduction of judicial reviews of involuntary commitment and the evolution of the ways public psychiatric institutions are funded. Unequally successful and traversed by heterogeneous institutional logics, from law and economics respectively, both changes aim to shape norms of the legitimate functioning of psychiatric hospitals. Hence, they contribute to changes in professional practices and organisational dynamics. This sociological work draws on interviews, conducted with medical and judicial professionals and policy makers, a set of ethnographic observations carried out in psychiatric hospitals and judicial hearings, as well as a review of written sources. The dissertation analyses the elaboration of public policies in psychiatry and their implementation, focusing on the role of psychiatrists and their interactions with other professionals, particularly in the legal field, as well as with institutional, national or regional actors. This work concludes that psychiatrists have been relatively dispossessed of control over the process of reform of the psychiatric institution over the last decades. However, the deprivation is masked by their ability to partly control the conditions of the implementation of these policies.